The history and future of bioethics a sociological view - Evans, John Hyde, 1965- (New York ; Oxford : Oxford University Press, 2012)
How do we as a society decide whether biotechnologies are ethical? For decades, professional bioethicists have served as a mediator. John H. Evans closely examines the history of the bioethics profession, and proposes a radical solution to the current crisis of mistrust.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Bioethics -- History